A potential role for CD25+ regulatory T-cells in the protection against casein allergy by dietary non-digestible carbohydrates. - Schouten, B; van Esch, B; Hofman, G; de Kivit, S; Boon, L; Knippels, L; Garssen, J; Willemsen, L (2012)
Dietary non-digestible carbohydrates reduce the development of cows' milk allergy in mice. In the present study, the contribution of CD25+ regulatory T-cells (Treg) was investigated using in vivo Treg depletion and adoptive transfer studies. Mice were orally sensitised with casein and fed a diet containing 2 % short-chain galacto-, long-chain fructo- and acidic oligosaccharides (GFA) or a control diet. Donor splenocytes of mice sensitised with casein and fed the GFA or control diet were adoptively transferred to naive recipient mice, which were casein- or sham-sensitised and fed the control diet. In addition, in vivo or ex vivo CD25+ Treg depletion was performed using anti-CD25 (PC61). The acute allergic skin response upon intradermal casein challenge and casein-specific Ig were determined. Furthermore, T-helper (TH) 1 and TH2 cell numbers were analysed in the mesenteric lymph nodes. The oligosaccharide diet strongly reduced the development of the acute allergic skin response, which was abrogated by the in vivo anti-CD25 treatment. The diet enhanced the percentage of TH1 cells and tended to reduce the percentage of TH2 cells in casein-sensitised mice. Recipient mice were protected against the development of an acute allergic skin response when transferred with splenocytes from casein-sensitised GFA-fed donor mice before sensitisation. Ex vivo depletion of CD25+ Treg abrogated this transfer of tolerance. Splenocytes from sham-sensitised GFA-fed donor mice did not suppress the allergic response in recipient mice. In conclusion, CD25+ Treg contribute to the suppression of the allergic effector response in casein-sensitised mice induced by dietary intervention with non-digestible carbohydrates.